Fundamentals of Electronics 3 : Discrete-Time Signals and Systems and Conversion Systems. - Muret, Pierre (John Wiley & Sons, Incorporated, 2018)
Over the last 60 years, electronics has undergone important and rapid developments. This has generated a large range of theoretical and practical notions. This book presents a comprehensive treatise on the evolution of electronics and allows the reader to grasp both the fundamental concepts and the associated practical applications through examples and exercises. Following on from Volume 1, which studied elementary devices, their electrical models and basic functions, Volume 2 was devoted to linear and stationary systems in the continuous-time regime. This third volume deals with the properties of discrete-time and quantized level systems over two chapters. The first presents an analysis of sampled signals and systems, with applications on switched capacitors circuits, analog and digital phase locked loops, frequency synthesis and filters characterized by either finite or infinite impulse response. Most tools are useful to elucidate the properties of both analog and digital systems. The second chapter focuses on the properties of analog-to-digital and digital-to-analog converters. Various principles that are used to perform these conversions are described. Finally, a large section is devoted to sigma-delta converters. Throughout this whole chapter, the signal-to-noise ratio, which is a central issue in these quantized level systems, is analyzed and discussed. Both chapters are followed by useful exercises which illustrate the general principles addressed. The exercises further build on the material covered in the chapters, particularly that which may not have been covered in detail. Book jacket.